2018
DOI: 10.1136/bmjopen-2017-018788
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of diagnostic tools and medications in acute rhinosinusitis in Spain: a population-based study (the PROSINUS study)

Abstract: ObjectivesAcute rhinosinusitis (ARS) has a high incidence. Diagnosis is clinical, and evolution is mostly self-limited. The aim of this study was to describe the sociodemographic characteristics and use of diagnostic tools and medications in patients with ARS.DesignThis is a prospective observational study in real-life clinical practice.SettingPatients with clinical diagnosis of ARS (n=2610) were included from ear, nose and throat clinics in Spain. A second visit at resolution was done.ParticipantsPatients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 55 publications
5
50
0
5
Order By: Relevance
“…Because the respiratory epithelium is the primary site of SARS-CoV-2 attachment and infection, as with many other respiratory viruses, it may not be surprising for COVID-19 to affect the olfactory neuro-epithelium having an impact on smell and flavour [42]. Recently, our team has demonstrated that two out of three patients with the common cold or postviral acute rhinosinusitis have impaired smell, this being associated with disease severity [16].…”
Section: Covid 19 and Olfactory Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the respiratory epithelium is the primary site of SARS-CoV-2 attachment and infection, as with many other respiratory viruses, it may not be surprising for COVID-19 to affect the olfactory neuro-epithelium having an impact on smell and flavour [42]. Recently, our team has demonstrated that two out of three patients with the common cold or postviral acute rhinosinusitis have impaired smell, this being associated with disease severity [16].…”
Section: Covid 19 and Olfactory Dysfunctionmentioning
confidence: 99%
“…-Postviral upper respiratory infection could be due to a combined conductive and sensorineural/inflammatory disorder [16].…”
Section: Loss Of Smell Etiologymentioning
confidence: 99%
“…Odor detection is related to the most peripheral part of the olfactory system [ 7 ], whereas identification and recognition memory involve cognitive tasks of central structures, such as the orbitofrontal region and other areas of the limbic system. In addition to viral etiology [ 8 , 9 ], several other causal factors have been described: posttraumatic events [ 10 12 ], neurodegenerative diseases [ 13 15 ], sinonasal inflammatory diseases (chronic rhinosinusitis, nasal polyps) [ 16 19 ], and allergic rhinitis (in adults [ 20 ] or children) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in ARS, the diagnosis is made on clinical grounds and CT is not recommended (191) unless the condition persists despite treatment or a complication is suspected, when contrast is used if there is no contraindication (223) . However, a recent study from Spain suggested that CT continues to be over-used in this context (224) .…”
Section: Recommendationsmentioning
confidence: 99%